Combined measurement and QCD analysis of the inclusive e ± p scattering cross sections at HERA - Aaron, FD; Abramowicz, H; Abt, I; Adamczyk, L; Adamus, M; Al-daya Martin, M; Alexa, C; Andreev, V; Antonelli, S; Antonioli, P; Antonov, A; Antunovic, B; et al. (Springer Verlag, 2010)
A combination is presented of the inclusive deep inelastic cross sections measured by the H1 and ZEUS Collaborations in neutral and charged current unpolarised e ± p scattering at HERA during the period 1994-2000. The data span six orders of magnitude in negative four-momentum-transfer squared, Q 2, and in Bjorken x. The combination method used takes the correlations of systematic uncertainties into account, resulting in an improved accuracy. The combined data are the sole input in a NLO QCD analysis which determines a new set of parton distributions, HERAPDF1.0, with small experimental uncertainties. This set includes an estimate of the model and parametrisation uncertainties of the fit result.